Hubungan Pendidik Dan Terdidik Dalam Al-Quran - Nurul Fatihah; Difla Nadjih (Universitas Cokroaminoto Yogyakarta, 2017)
What the relationships is like between educator and learner have actually been given in the Qur'an. Hamka is basically not a specialist in the field of education, inspite of this, he has heartedly investigated the aforementioned relationships as revealed in his monumental book of commentary, Tafsir al-Azhar, especially in Surat al-Alaq Verse 1-5. The relationships is build-up based on a pattern of learner-centered education which is different from educator-centered education pattern. The former is characteristically modern and the latter pattern is traditional in orientation. As an oustanding public figure raised-up in a religious environtment and actively engaged in struggle with the modernists movement in Indonesia, it is only natural that Hamka emphasizes the learner-centered pattern of education which is widely seen as a modern educational trend.